University Spin-Off's Transfer Speed: Analyzing the Time from Leaving University to Venture - Kathrin Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
For academic spin-offs I analyze the length of time between the founder's leaving of academia and the establishment of his firm. Technology transfer can take place even years after leaving the mother institution. A duration analysis reveals that a longer time-lag is caused by the necessity of assembling complementary skills, either by acquisition by a single founder or by searching for suitable team members. Furthermore, new ventures are established earlier if the intensity of technology transfer is high, the founders have access to university infrastructure, or received informal support by former colleagues.
Keywords: L26; J24; C41; M13; 330; academic spin-offs; technology transfer; skill complementarities; Unternehmensgründung; Forschungskooperation; Betriebsaufspaltung; Technologietransfer; Dauer; Unternehmer; Weiterbildung; Deutschland